“Diagnóstico de enfermedades en el cultivo de pepinillo (cucumis sativus), bajo dos sistemas de manejo, en la provincia de Lamas-Perú” - Gonzales Oávila, Max Erix (2008)
Karina de el Pilar Fasanando Inga. Performance Academioo and its relationship with the violence and the communication family in students in the fifth grade of secondary. C.E. "Santa Rosa" Tarapoto - 2002, Universidad Nacional de San Martín. Thesis 2003. The purpose of the present study type retrospective, descriptive design oon correlates!, was to determine the relationship that "Santa Rosa" in the District of Tarapoto, exists between academic performance and violence and family oomunicacion in the fifth grade of secondary education of State College students during the afø of 2002. The universe shows! It was formed by 291 students of both sexes enrolled in the fifth grade of secondary education, those who applied the survey in order to determine the academic performance, and violence, and family communication, to finally find the relationship between the variables concerned. Is arrived at the following conclusions: not is obtained evidence significant as to...